Large-Area Nanopillar Arrays by Glancing Angle Deposition with Tailored Magnetic Properties - Escrig-Murua, J; Tejo-Lazo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Ferromagnetic films down to thicknesses of tens of nanometers and composed by poly-crystalline Fe and Fe2 O3 nanopillars are grown in large areas by glancing angle deposition with magnetron sputtering (MS-GLAD). The morphological features of these films strongly depend on the growth conditions. Vertical or tilted nanopillars have been fabricated depending on whether the substrate is kept rotating azimuthally during deposition or not, respectively. The magnetic properties of these nanopillars films, such as hysteresis loops squareness, adjustable switching fields, magnetic anisotropy and coercivity, can be tuned with the specific morphology. In particular, the growth performed through a collimator mask mounted onto a not rotating azimuthally substrate produces almost isolated well-defined tilted nanopillars that exhibit a magnetic hardening. The first-order reversal curves diagrams and micromagnetic simulations revealed that a growth-induced uniaxial anisotropy, associated with an anisotropic surface morphology produced by the glancing angle deposition in the direction perpendicular to the atomic flux, plays an important role in the observed magnetic signatures. These results demonstrate the potential of the MS-GLAD method to fabricate nanostructured films in large area with tailored structural and magnetic properties for technological applications. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.